Analisis Media Dadu dalam Penulisan Teks Negosiasi Siswa Kelas X MA Al-Muttahidah - Indah Lestari; Wahyu Lestari; Ahmad Ilzamul Hikam (Universitas Wijaya Kusuma Surabaya, 2026)
This study aims to describe the learning strategy that utilizes dice media in teaching negotiation text writing, the challenges encountered during its implementation, and the teacher's contribution in improving the participation of tenth-grade students at MA Al-Muttahidah. This research employed a qualitative approach with a descriptive study design. The participants consisted of an Indonesian language teacher, tenth-grade students, and the vice principal for curriculum affairs. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings revealed that the use of dice media through a game-based learning approach helped students explore ideas, determine themes, and creatively construct negotiation dialogues. The implementation of dice media also created a more dynamic learning environment, as students became more actively involved in discussions and group activities. However, several challenges were identified during the implementation, including students’ lack of self-confidence, difficulties in organizing the structure of negotiation texts, and limited instructional time. Furthermore, the teacher played a crucial role as a facilitator, motivator, and classroom manager in supporting students’ participation throughout the learning process. Therefore, dice media can serve as an effective alternative instructional medium for teaching negotiation text writing.